Activities Of MGMP IPA Activities to Increase the Teacher Competence in Bogor District - Wiworo Retnadi Rias Hayu; Anna Permanasari; Omay Sumarna; Sumar Hendayana (Universitas Djuanda, 2019)
MGMP is a community of teachers to always learn (long life learning). Rapid development of the times requires the teacher to participate in the pursuit of knowledge. Lifelong learning is the teacher's obligation to generate knowledge. This is necessary because the teacher is a facilitator of students to gain knowledge. In line with that, teachers are expected to master every change process so students can also face global challenges. These results indicate that the majority of teachers who come to MGMP IPA Bogor District civil servants Teachers. MGMP activities are a place that facilitates teachers' mutual learning together. MGMP members consist of various teachers from different schools. The results show the MGMP majority forum of senior teachers. Senior Teachers are expected to guide junior and mediator teachers to learn from one another. The results of the study concluded that continuing professional development needs to be developed, then content, then creativity, ICT and finally SK and KD to improve teacher competence. The activity steps are arranged to help activate and optimize activities, namely by self-development, scientific publications, and scientific work in the Bogor District MGMP.